Processos estruturantes no Brasil: origem, conceito e desenvolvimento - Domingos, Pedro Luiz de Andrade (2019)
There is a great academic debate around the Brazilian Civil Procedure Code (2015), stimulating discussions that propose a rational and coherent unity of interpretation of rights, in order to respond to the legitimate expectation of a civil justice appropriate to the present time. To reflect on the design of procedural models for special conflicts, it is necessary to ask how courts judge their cases and how the application of specific performance in legal resources contributes to greater efficiency in decision-making on substantive law. The research aims to address the origin, conception, and procedural development of structural injunctions for complex cases in public law litigation. A comparative study will be carried out from four perspectives: (1) The historical survey of the new litigation model in the USA, and the incorporation of these ideas by the Brazilian academy in their own legal system; (2) The systematization of aspects that can be approached as common points to identify it and that help to adapt its use in the national legal system; (3) The survey of the characteristics in this special litigation, which allows to verify a standard behavior for guiding the adjudication by the courts, demonstrating the use of this specific performance for the protection of rights, and the main differences between this form of litigation and the ordinary litigation. Towards the end of the research, we expect to (4) show the repositioning of the theoretical debate on structural injunctions in the United States, as a result of a decision maker to review institutional behaviour in the context of a complex litigation. Subsequently, we proposed that a form of cooperative procedure in the Brazilian legal system, is suitable to receive these proposals.